A cross-sectional study exploring the predictors of herpes zoster vaccination for people aged over 50 years old in Chaoyang district, Beijing - Jiao Zhang; Shuo Zhang; Bin Jia; Yunhua Bai; Zhen Li; Fang Liu; Yingxue Hu; Xiaojing Guo; Jianxin Ma; Shuming Li; Qian Shi (Frontiers in Public Health)
BackgroundVaccination is an effective measure to prevent herpes zoster and its related complications. The coverage of herpes zoster vaccination is extremely low in China, and there is a notable lack of research investigating the barriers to promoting the herpes zoster vaccine in China.ObjectivesThis study aims to survey the status of herpes zoster (HZ) vaccination and its associated factors among individuals aged 50 years and older, it also seeks to identify the barriers to vaccination and dissemination, thereby providing a scientific foundation for enhancing the vaccination rate of herpes zoster.MethodsFrom March to August 2023, a questionnaire survey was conducted using a multi-stage sampling method on permanent residents aged 50 years and older in Chaoyang district of Beijing. Logistic regression analysis and decision tree models were employed to explore the predictors herpes zoster vaccination behavior.ResultsThe herpes zoster vaccination coverage was 13.26% (403/3040), with 52.4% of respondents expressing willingness but not yet receiving the vaccine, while 34.31% (1,043/3040) were unwilling to be vaccinated. Among those willing but not vaccinated, 48.06% cited high cost as the reason for abstaining from vaccination. Multivariate logistic regression analysis revealed that certain factors were associated with lower vaccination coverage, including being female, having a low frequency of influenza episodes (less than twice per year), and having chronic diseases. On the other hand, higher vaccination coverage was observed among individuals whose spouses had a master’s degree or higher, those awarded that a history of chickenpox may lead to potential herpes zoster infection, those who were knowledgeable about the herpes zoster vaccine, and those received recommendations from medical staff. Additionally, the decision tree model confirmed that recommendations from medical staff had the most significant impact on vaccination.ConclusionThe survey reveals a generally low vaccination coverage of the herpes zoster vaccine among residents aged over 50 in this area. It is recommended to enhance the role of medical staff in advocating for vaccination, conduct community-based educational initiatives that focus on varicella, herpes zoster, and related knowledge, and alleviate the financial burden to improve the herpes zoster vaccination coverage.